PENGARUH TINGKAT BUNGA SERTIFIKAT BANK INDONESIA (SBI) DAN PEMBAYARAN NON TUNAI TERHADAP PERMINTAAN UANG DI INDONESIA - Donna Anggia Priscylia (Jurnal Ekonomi Pembangunan, 2014)
This research aimed to examine the effect of SBI Interest Rates and Non-Cash Payment on Money Demand in Indonesia. Money controls the economy, if there is excess money there will be inflation and if there is lack of money there will be deflation. Demand for money is influenced by the interestÂ rate of Bank Indonesia Certificate and in line with technology development in communication and information, then it replaces the pattern of public payment from cash payment to non-cash payments also affects money demand. The data used is the Money Demand (M1), SBI Rate (ISBI), and the transaction value of BI-RTGS and Clearing as a parameter of Non-Cash Payment. The analytical method used is ordinary least squares regression with ECM method and good estimation results with the classical assumption test. The results show that the rate of SBI has a significant negative impact and Non-Cash Payment has significant positive impact on Money Demand in Indonesia. Keywords: M1, SBI Rate, Non-Cash Payments, BI - RTGS, Clearing, ECM